Contribuição para avaliação dos tipos de relatórios de auditoria: um estudo voltado às empresas listadas na BM&FBovespa entre 2011 e 2015 - Gilioli, André (2017)
The current events and financial scandals happening in Brazil and in the world, have aroused greater interest in the independent auditor’s work results, which represents an important and fundamental role for the ever-evolving capital market; therefore, knowing how auditors and companies have developed and presented their audit reports is a way to measure this evolution, thus broadening the horizons of stakeholders even more. Knowing that, the goal of this study is to categorize and identify what are the types of audit reports and to verify which companies are the ones that most sign the reports published by the companies listed on the BM&FBovespa between 2011 and 2015. To reach the goals of this research, a population composed by each and every publicly traded company, with shares in the Stock Exchange in São Paulo, was selected. We used bibliographic research techniques, data collection, descriptive analysis and documental analysis technique, which allowed the verification and categorization of 2,386 audit reports. Among them, it was found that the Big Four (PWC, EY, KPMG and Deloitte) tend to issue more reports without remarks when compared to the Non-Big-Four, which total 97 audit firms, which leads to consider that clients Of Big Four companies support accounting conservatism and are less likely to have remarks in their reports